2006
DOI: 10.5144/0256-4947.2006.192
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prescribing information for generic drugs manufactured in the Middle East and marketed in Saudi Arabia

Abstract: BACKGROUNDLittle research has assessed the quality of manufacturer-provided prescribing information or documented differences in key aspects of drug information among different marketed generic products of the same drug, particularly in the Middle East and Arabian Gulf. We assessed the quality of written prescribing information for selected generic drugs marketed in Saudi Arabia and manufactured in various countries of the Middle East.METHODSWe assessed the correctness and completeness of information pertainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Inadequate information in the PPIs has been reported by authors in different countries. In a study carried out in Saudi Arabia, the authors found that there was substantial disagreement in information between generic package inserts and the British National Formulary and the package inserts of the brand products marketed in Saudi Arabia 6. In the USA, it was shown that PPIs do not fully meet the federal regulations 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate information in the PPIs has been reported by authors in different countries. In a study carried out in Saudi Arabia, the authors found that there was substantial disagreement in information between generic package inserts and the British National Formulary and the package inserts of the brand products marketed in Saudi Arabia 6. In the USA, it was shown that PPIs do not fully meet the federal regulations 20.…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, the PPI is considered an important source of drug information for healthcare providers as well, because of a limited ability to access up to date drug information resources. Even though it is an important source of information, several studies from different countries have shown a need to improve the content and readability of the PPI 1,2,3,4,5,6,7,8. Despite efforts to improve the readability and comprehensibility, by both the drug regulatory authorities and the manufactures, package inserts are still criticized 1,3,4,5.…”
Section: Introductionmentioning
confidence: 99%
“…However, this figure was actually the total number of men who died in the camp in 1918 from all causes as reported by the Principal Medical Officer at the camp [3]. Further examination of data on the cause of death and date-of-death suggests the total mortality attributable to this outbreak was 163 [5]. This revision gives a fairly conservative figure for the mortality impact and it is the one that we have used in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies, particularly in the Middle East, have found disagreement between patient information leaflets in some medicine samples when compared with national formularies. 106,107 Therefore, the addition of patient information leaflets to examination of medicine samples in medicine quality survey studies is open for debate among the scientific community.…”
Section: Type Of Analysis Used In Ssffc Surveysmentioning
confidence: 99%